LITERATURE AS A CATALYST FOR CHANGE: BUILDING TOLERANCE THROUGH BUGIS-MAKASSAR CLASSICAL LITERATURE - Amiruddin, Nurlina (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This article examines Bugis-Makassar classical literature as a catalyst for social change, specifically in building tolerance through a literary sociology approach. The research aims to describe the values that foster tolerance in Bugis-Makassar classical literary works such as pappaseng (wise advice) in sureq, lontara’ (ancient manuscripts), folktales, and kelong (traditional songs). This study employs a literary sociology approach with a focus on three main aspects: sociology of the author, sociology of the work, and sociology of the reader. The research method used is descriptive qualitative. The data collection technique for this study is listening and recording. Data analysis uses a descriptive analytical method. The findings indicate that social values that promote tolerance in community life are found in Bugis-Makassar classical literary works such as pappaseng (wise advice) in sureq, lontara’ (ancient manuscripts), folk tales, and kelong (traditional songs). The conclusion of this study is that Bugis-Makassar classical literature can serve as a moral compass and a collective memory that shapes the Bugis-Makassar community’s perspective on differences. These values are not merely theoretical concepts but are also applied concretely in daily life, thus becoming a foundation for maintaining social relations, which proves that Bugis-Makassar classical literature plays a vital role in fostering tolerant attitudes as an agent of change today.